(untitled) (Sciences & Technologie. C, Biotechnologies, 2004)
The optimal mode of urinary tract reconstruction following cystectomy continues to challenge the urologic surgeon. We describe the experimental application and histological compatibility of the demucosalized ileum with his vascular supply, in the reconstruction of continent neobladder, after three years post operative follow up.